Correlação entre as classificações de Pfirrmann e Modic na degeneração do disco intervertebral lombar - Leite, Marcio Squassoni [UNIFESP] (2010)
OBJECTIVE: to correlate the changes found in the lumbar magnetic resonance imaging according to Modic and Pfirrmann classifications. METHODS: lumbar spine resonances of 54 outpatients were selected (23 men and 31 women), who were already under investigation because of their comorbidity. According to their degree of Pfirrmann classification, 264 intervertebral discs (L1 to S1) were classified. The presence of signal abnormalities of the vertebral body was recorded as Modic classification. The χ2 mwas applied, adopting significance levels below 0.05 (a=5%). RESULTS: The mean age studied was of 48.4 years (26-77 years). A higher prevalence of Pfirrmann type IV (31.1%) was observed. In 88.3% of the sample, Modic was absent, and also Modic 3; 60% of Modic 2 was related to Pfirrmann type V, and 36.4% of Modic 1 was equally distributed among Pfirrmann type IV and V. Statistically significant association between Modic changes and Pfirrmann (p<0.001) was found. CONCLUSION: there was a clear association between the classifications studied, comparing the stages of Pfirrmann (IV and V) with Modic type 1 and 2.